A new species of Atrichopogon Kieffer from northern Argentina (Diptera: Ceratopogonidae) - Marino, Pablo Ignacio (2003)
Atrichopogon carpinteroi, n. sp. from the Argentinian province of Formosa is described and illustrated from male and female specimens collected with a light trap. The species, easily recognized by the contrasting coloration between the thorax and abdomen, lacks secondary sexual dimorphism. It is compared with the congeners, A. utricularis Macfie and A. homofacies Spinelli.